Astronomical observations in the Inca Temple of Coricancha (Cusco)? A critical review of the hypothesis - Ziółkowski, Mariusz; Kościuk, Jacek (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
Coricancha (Qurikancha, Qorikancha) was the most important temple in Cuzco, the capital of Tawantinsuyu, the Inca Empire. The Spanish Conquistadores had the opportunity to see her, and her legendary richness, in November 1533, after entering Cuzco. Coricancha was the place to worship the most sacred effigies of the Inca cult, including the figure of the Sun, called Punchao. From this early period, there are also references, unfortunately not very precise, related to a specific orientation of some elements of the temple providing reflection of the rising (or setting) sun on the aforementioned figure of Punchao. Based on these sources, and the analysis of the remains of the original Inca Coricancha, a number of hypotheses regarding the possible astronomical function of this temple were formulated. Of particular importance was the hypothesis of Zuidema and Aveni, according to which astronomical observations at Coricancha constituted the structural skeleton of a specific Inca calendar cycle of 328 days. This article presents a critical analysis of this hypothesis, based on long-term research and measurements carried out in the Coricancha by the authors of the text.